International competition intensified: Job satisfaction sacrificed? - Barbara Dluhosch; Daniel Horgos (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2016)
There has been an intense debate as to the effects of offshoring and global value chains on labor, with the debate centering around possible negative employment and income effects for the low(er) skilled in advanced economies. Although sociological and psychological research has shown that income falls far too short when it comes to subjective well-being (SWB), the globalization's impact on SWB has been surprisingly under-researched. This applies in particular to job satisfaction, including of those negatively affected by seeing their real income depressed. Against this backdrop, we develop a trade model that is capable of capturing job satisfaction in conjunction with the income and distributional effects of offshoring. Contrary to a great many beliefs, our theoretical considerations suggest that those remaining employed may be more satisfied with their jobs, even if suffering from increased competition and from more tasks being offshored. Running a cross-section logistic regression model that combines information on offshoring and job satisfaction, lends support to our theoretical explanations. Accordingly, job satisfaction is on average rated higher in countries with comparatively high offshoring activities. More disaggregated regressions get to the heart of the matter, which is a change in the characteristics of the remaining jobs. Our results stand up to extensive robustness checks with respect to different specifications, measures of globalization, and even when controlling for many of the usually suspected variables with reference to SWB.
Keywords: F66; I31; 330; Subjective Well-Being; Job Satisfaction; Offshoring; Global Value Chains